An efficient post-installed shear-strengthening solution for RC structural elements - Medeghini Filippo; Ahrens Mark Alexander; Palmeri Alessandro; Singh Amol; Mark Peter (MATEC Web of Conferences, 2025)
Much of Europe’s building stock and infrastructure were constructed in the last century, often before strict design standards were adopted. Ageing materials, increased loading demands, sustainability requirements, and cost-efficiency goals further support the need for the retrofitting of existing reinforced concrete (RC) structures rather than their demolition and replacement. Motivated by these considerations, a new post-installed (PI) shear strengthening system was developed. In this solution, threaded rods bonded in drilled holes act as a substitute for traditional cast-in (CI) stirrups. An extensive experimental campaign consisting of several large-scale beams was executed to rigorously assess and quantify the new system’s performance, leading to a “general construction technique permit” in Germany (Allgemeine Bauartgenehmigung, aBG). The campaign investigated experimentally the main parameters that influence the shear resistance in RC beams, namely: shear and longitudinal reinforcement ratios, effective depth, and concrete compressive strength. The longitudinal rebars in tension were instrumented, allowing detailed tracking of strains during all tests. Results were compared with current Eurocode 2 provisions for concrete members with shear reinforcement, demonstrating that the shear resistance mechanism of the new PI solution closely matches that of conventional CI stirrups, with similar structural performance, highlighting its effectiveness as an efficient retrofitting solution.